2021
DOI: 10.3892/mmr.2021.12241
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA profiling reveals a potential role of hsa_circ_IPCEF1 in papillary thyroid carcinoma

Abstract: Circular RNAs (circRNAs) are a novel type of non-coding RNAs that are expressed across species and are implicated in cellular biological processes, displaying dysregulated expression in various tumorigeneses. Therefore, circRNA deregulation could be a crucial event in thyroid carcinoma. The present study identified circRNA signatures in several patients with papillary thyroid carcinoma (PTC) to complement the understanding of PTC pathogenesis. Using microarray technology, the circRNA profiles in three pairs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…In contrast, circ-ITCH is downregulated in PTC tissues and cell lines, and its expression levels are significantly associated with LNM (p = 0.020), clinical stage (p = 0.022) (Wang M. et al, 2018). Similarly, hsa_circ_IPCEF1 is significantly decreased in both PTC tissues and blood, and its levels were positively correlated with LNM (p < 0.001) (Guo et al, 2021). Most studies have reported that there is no relationship between circRNA levels and gender in TC.…”
Section: Circrnas As Promising Diagnostic and Prognostic Biomarkers F...mentioning
confidence: 92%
See 3 more Smart Citations
“…In contrast, circ-ITCH is downregulated in PTC tissues and cell lines, and its expression levels are significantly associated with LNM (p = 0.020), clinical stage (p = 0.022) (Wang M. et al, 2018). Similarly, hsa_circ_IPCEF1 is significantly decreased in both PTC tissues and blood, and its levels were positively correlated with LNM (p < 0.001) (Guo et al, 2021). Most studies have reported that there is no relationship between circRNA levels and gender in TC.…”
Section: Circrnas As Promising Diagnostic and Prognostic Biomarkers F...mentioning
confidence: 92%
“…RNA-seq, circRNA-specific microarrays and bioinformatics analyses are the most commonly used methods for genomewide profiling of circRNAs, and thousands of circRNAs have been identified in tissues, cells, exosomes, and blood of patients with TC (Table 1) (Peng et al, 2017;Hou et al, 2018;Lan et al, 2018b;Ren et al, 2018;Yang et al, 2019;Chu et al, 2020b;Liu et al, 2020b;Liu Q et al, 2020;Long et al, 2020;Sun J. W. et al, 2020;Yang W. et al, 2020;Yang Y. et al, 2020;Yu et al, 2020;Chu et al, 2021;Guo et al, 2021;Li et al, 2021b;Lv et al, 2021;Qiu et al, 2021;Zhang et al, 2022). Hundreds of differentially expressed circRNAs (DECs) were identified between the tumour and non-tumour groups.…”
Section: Circrnas Expression Profiles In Tcmentioning
confidence: 99%
See 2 more Smart Citations
“…IPCEF1 was viewed as a significant biomarker for PTC. Moreover, a study showed that the hsa_circ_IPCEF1/hsa-miR-3619-5p axis was associated with the mechanism of PTC, which offers a new idea for further diagnosis and treatment of PTC (Guo et al, 2021). Several researchers revealed noticeable differences in Trefoil factor 3 (TFF3) between benign thyroid nodules and thyroid malignancy (Krause et al, 2008;Karger et al, 2012).…”
Section: Figurementioning
confidence: 99%